Pengaruh Citra Merek, Kualitas Produk dan Harga Terhadap Keputusan Pembelian Mie Sedaap - Amandus Edi Gunawan (2021)
This study uses a quantitative description method which is carried out on Sedaap instant noodle products. Mie Sedaap is one of the famous instant noodles among Indonesian people. The purpose of this research is to find out and prove whether purchasing decisions on this delicious noodle product are influenced by brand image, product quality and price. The population in this study are the consumers of Mie Sedaap who live in Pondok Labu. Samples were taken as many as 75 respondents with non-probability sampling method. By distributing questionnaires to consumers of delicious noodles at the pumpkin cottage during the data collection process. The data analysis technique used is descriptive analysis and inferential analysis with the analytical tool used is PLS (Partial Least Square). The results showed that the variable brand image and significant effect on purchasing decisions, while product quality and price variables have no effect and are not significant on purchasing decisions. Keywords : Brand Image, Product Quality, Price, Purchase Decision